Urban environmental heath: respiratory infection and urban factors in urban growth corridor of Petaling Jaya, Shah Alam and Klang, Malaysia - Oliver Ling, Hoon Leh; Siti Nur Afiqah Mohamed Musthafa; Abdul Rauf Abdul Rasam (Universiti Kebangsaan Malaysia, 2014)
Environmental health in general is referring to the aspect of concern on healthy environment, and the interrelations between environment and human health. Due to the urbanization, urban development is changing the natural environment into a man-made environment. Along with the process, level of environmental quality and human health are decreased. Air quality as reference shows that urban ambient air is more polluted than rural. Due to high density of human population and their activities in urban areas, it produces air pollutants with higher rate as compared to less-developed areas. Air pollutants contribute to various health problems. People suffering from respiratory diseases are the most likely to be affected by air pollution. This paper aimed to examine the rate of respiratory infection among residents in an urban growth corridor (Petaling Jaya-Shah Alam-Klang) and the relationship with the urban land uses, traffic volume and air quality. There were four major types of data used in this study i.e., respiratory infection of the respondents, air quality, land use and traffic volume. A health questionnaire survey was carried out besides the secondary data collection from the various government departments. Relationship analysis was performed between respiratory health and the urban factors (air quality, traffic volume and land uses). The study found out that the relationship between the respiratory health and the urban factors is different in city-wide land use and traffic factors, as compared to the localised air quality and land use factors. To conclude, the urban factors are potentially affecting the respiratory health.